2008
DOI: 10.1016/j.asoc.2007.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of cells to switches in a cellular mobile network using a hybrid Hopfield network-genetic algorithm approach

Abstract: Handoff and cabling cost management plays a key role in the design of cellular telecommunications networks. The efficient assignment of cells to switches in this type of networks is an NP-complete problem which cannot be solved efficiently unless P = NP. This paper presents a hybrid Hopfield network-genetic algorithm approach to the cell-to-switches assignment problem, in which a Hopfield network manages the problem's constraints, and a genetic algorithm searches for high quality solutions with the minimum pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…HYSA üzerindeki çalışmalar temel olarak donanımsal uygulama ve öğrenme algoritması geliştirme olarak sınıflandırılabilir. Genelleştirilmiş bir öğrenme algoritması elde etme çalışmaları günümüzde halen sürmektedir [3][4][5].…”
Section: Giriş şunclassified
“…HYSA üzerindeki çalışmalar temel olarak donanımsal uygulama ve öğrenme algoritması geliştirme olarak sınıflandırılabilir. Genelleştirilmiş bir öğrenme algoritması elde etme çalışmaları günümüzde halen sürmektedir [3][4][5].…”
Section: Giriş şunclassified
“…Instead, we develop an efficient algorithm based on GA, namely SR2CAB-GA, to solve the addressed problem. The reason is that GA is a robust search technology and recently has been validated to be suitable for the allocation problems [15,16], such as Lin and Yeh [7,8], Lee et al [17], Salcedo-Sanz et al [18], Salcedo-Sanz and Yao [19], Kaminer and Ben-Asher [20]. In the proposed algorithm, a two-class allocation is represented as a chromosome (a solution), and system reliability is evaluated in terms of MPs and state-space decomposition.…”
Section: Introductionmentioning
confidence: 98%
“…Let   be the Euclidean distance between BS i and MSC m, then the cabling cost   is defined as    ⋅  , where  is a positive multiplier. <Figure 2> and <Table 1> show the examples of the distance   between BS and MSC (Salcedo-Sanza and Yaob, 2008). We assumed that the handover cost is in proportional to the handover traffic.…”
Section: Computational Experimentsmentioning
confidence: 99%
“…Several other heuristic techniques have been applied to the similar problem, such as Tabu Search (TS) (Pierre and Houéto, 2002), Simulated Annealing (Menson and Gupta, 2004), Genetic algorithm (Salcedo-Sanza and Yaob, 2008). Dianati et al (2003) suggested a Genetic based solution procedure for the problem.…”
Section: Introductionmentioning
confidence: 99%